The role of circulating blood microRNA-374 and microRNA-10 levels in the pathogenesis and therapeutic mechanisms of major depressive disorder. (15th October 2021) - Liu, Wanying; Zhang, Fuxu; Zheng, Yanqun; He, Shen; Zhang, Tianhong; Guo, Qian; Xu, Hua; Chen, Haiying; Liu, Caiping; Yu, Shunying; Jiang, Kaida; Li, Huafang; et al.
Highlights: A total of 17 miRNAs were screened out to be differentially expressed in medication-naïve MDD patients compared to HC. miR-374b and miR-10a expression differed between MDD patients and controls. miRNAs may serve as biomarkers for treatment response in major depressive disorder. Abstract: Compelling recent evidence suggests that microRNAs (miRNAs) regulate specific mRNA transcripts at the transcriptomic level and coordinately influence complex regulatory networks, which may play a crucial role in the pathogenesis of major depressive disorder (MDD) and the treatment effects of antidepressants. To evaluate the possible involvement of miRNAs in the pathophysiology and therapeutic response of MDD, we conducted a miRNA expression array analysis of the peripheral blood mononuclear cells (PBMCs) of 5 depressed patients and 5 healthy controls (HCs). Subsequently, we chose 2 miRNAs for validation with real-time PCR (RT-PCR) analysis pre- and post-treatment in another group of 25 MDD patients and 25 HCs. In the array, 5 miRNAs were differentially expressed in medication-naïve MDD patients compared to HCs, of which 2 miRNAs were upregulated and 3 were downregulated. Furthermore, in comparison with HCs, MDD patients showed significantly lower expression levels of miR-374b and miR-10a before treatment. After 8 weeks of antidepressant treatment, both miR-374b and the miR-10a expression levels in MDD patients were significantly elevated only in responders. In conclusion, these results indicate the involvement of miR-374b and miR-10a in the biological mechanisms and therapeutic response of MDD, and provide new insights for exploring miRNAs as potential biomarkers for MDD.